Lack of knowledge of stakeholders in the pork value chain: Considerations for transmission and control of Taenia solium and Toxoplasma gondii in Burundi - Salvator Minani; Jean-Bosco Ntirandekura; Koen Peeters Grietens; Anastasie Gasogo; Sarah Gabriël; Chiara Trevisan (PLoS ONE, 2025)
Taenia solium and Toxoplasma gondii are important foodborne zoonotic parasites that cause substantial health and economic impacts worldwide. In Burundi, there was a lack of data on the knowledge, attitudes, and practices of stakeholders in the pork value chain. To fill this gap, this study aimed to assess the knowledge of stakeholders in the pork value chain regarding T. solium and T. gondii infections and identify health-seeking routes and factors contributing to parasitic transmissions. A mixed methods study was conducted in Bujumbura city, Kayanza, and Ngozi provinces from January 10 to April 27, 2023. Quantitative data was collected using questionnaire-based interviews with 386 participants, while qualitative data was gathered from 63 participants through focus group discussions, informal conversations, and observations. The majority of the participants in the quantitative study had heard about porcine cysticercosis (94.8%) and pork tapeworm (90.9%), although the transmission and symptoms of these diseases were less known (>60%) and inaccurately described. Most participants were not aware of human cysticercosis (96.4%), its association with epilepsy (78%), and T. gondii infections (91.2%). There was a low proportion of medical consultations for pork tapeworm (30.1%), epilepsy (36.5%), and toxoplasmosis (7%). The qualitative study supported the findings of the quantitative study, revealing low knowledge among participants and misconceptions about the causes, consequences, and treatment-seeking routes related to T. solium and T. gondii infections. The short roasting time of pork (<15 minutes) and low perception of the consequences of consuming pork infected with cysts exposed pork consumers to these parasitic infections. Inadequate knowledge about these parasitic infections, along with inadequate practices in treatment-seeking and pork preparation and consumption, can contribute to continued transmission and pose significant barriers to control programmes. Training and public health education following the One Health approach are urgently needed to better tackle these parasitic infections in Burundi.